Visitar, sentir e experimentar a pintura de Pedro Calapez - Vilhena, Joana da Cunha e Costa Consiglieri de, 1972- (2018)
The main goal of this article is to feel and to experience the painting by the Portuguese visual artist Pedro Calapez, in Art Education, in particular Visual Arts, in Portugal, mainly, in teacher training college. It is a study about the artistic experience through the sensation of painting in space of a gallery. The students feel and experience the process of creation as way of ‘sensation of colour’. This activity might provide the students to have a deep conscience through the artistic knowledge of the National Curriculum and Classroom